Evaluation of various antibiotics on growth rate and feed efficiency by finishing pigs - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials involving 300 finishing pigs (120-220 lbs.) were conducted to evaluate Tylan, Stafac, Lincomix, and Flavomycin by growth rate and feed efficiency. In trial I, none of the antibiotics improved growth rate or feed efficiency. In trial II, where pigs were more crowded, feeding an antibiotic slightly, but not significantly, increased daily gain (0 to 8% improvement) and feed efficiency (3 to 9%), with no significant difference among antibiotics. These studies demonstrate that the response or lack of response to feeding low levels of antibiotics during the finishing phase will depend on the level of stress imposed.
Keywords: Swine; Antibiotics; Growth rate; Feed efficiency; Finishng pigs